PRAWO RZYMSKIE JAKO ŹRÓDŁO PRAWA W AFRYCE POŁUDNIOWEJ - Mańko, Rafał (Zeszyty Prawnicze, 2017)
ROMAN LAW AS A SOURCE OF LAW IN SOUTHERN AFRICA Summary Roman law is usually regarded as an object o f historic study and not as a practical discipline of the legal science. However, the situation is different in six South African states - the Republic of South Africa, Zimbabwe, Lesotho, Swaziland, Botswana and Namibia - which have preserved the uncodified ius commune europaeum brought by the Dutch to the Cape of Good Hope in the 17th century. The hierarchy of the fontes iuris oriundi in the South African legal system seems to be the following: the Constitution, statutes, customary law, case-law, Roman-Dutch law and Roman law. The position occupied by Roman law is in fact only subsidiary, however it is a source of law and is referred to from time to time in the case-law. On the other hand it permeates the whole legal system which is based on fundamental notions derived from Roman law, which have been preserved and developed in the treatises of the Roman-Dutch jurists and the case-law of the courts. The frequency o f citations of Roman law in the South African case-law has been an object of two major studies. One, conducted by Van Der Merve concerned the period 1970-1979, the other, by Du Plessis - took into account the cases of 1990-1991. The studies revealed that Roman sources are cited in 4,7-4,8% of the case-law. According to another study by Zimmermann, only in half o f those cases the Roman sources were relevant for deciding the case. Nevertheless, it is submitted that these figures should be treated as significant, especially when compared with the position occupied by Roman sources in the modern case law in other civilian jurisdictions.